2012
DOI: 10.1126/science.1218831
|View full text |Cite
|
Sign up to set email alerts
|

Human α-Defensin 6 Promotes Mucosal Innate Immunity Through Self-Assembled Peptide Nanonets

Abstract: Netting the Bad Guys Antimicrobial peptides are an evolutionarily conserved component of innate immunity in the intestine. One family, α-defensins, typically exert their antimicrobial effects through microbicidal activity against bacteria. Humans express only two α-defensins, human defensin 5 (HD5) and HD6. HD5 exhibits bactericidal activity and plays a role in shaping the bacterial composition of the gut. HD6, on the other hand, does not show bactericidal activity and its function in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
431
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(446 citation statements)
references
References 31 publications
13
431
0
2
Order By: Relevance
“…This strongly suggests that, as in vertebrates, oyster ETs participate in host defense by capturing large numbers of microbes and preventing their dissemination (16). Surrounding and entangling of bacteria in DNA or peptide networks are indeed increasingly recognized as conserved mechanisms of antimicrobial defense (31). Moreover, as shown in some vertebrates, the antimicrobial properties of the ET-associated antimicrobials including histones (Table 1) and their concentration on ETs could also contribute to kill the entrapped microorganisms (10,16,19).…”
Section: Discussionmentioning
confidence: 99%
“…This strongly suggests that, as in vertebrates, oyster ETs participate in host defense by capturing large numbers of microbes and preventing their dissemination (16). Surrounding and entangling of bacteria in DNA or peptide networks are indeed increasingly recognized as conserved mechanisms of antimicrobial defense (31). Moreover, as shown in some vertebrates, the antimicrobial properties of the ET-associated antimicrobials including histones (Table 1) and their concentration on ETs could also contribute to kill the entrapped microorganisms (10,16,19).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence, however, has established that some proteins self-assemble into amyloid fibrils that carry out biological roles in the absence of pathology and are known as functional amyloids (Fowler et al, 2007;Pham et al, 2014). In mammals, these include premelanosome protein (PMEL), whose amyloid functions as a scaffold for the synthesis of melanin, several hormones that are stored as amyloids in the pituitary gland, RIP1 and RIP3 (receptor-interacting proteins 1 and 3) amyloids involved in programmed necrosis and α-defensin that forms an amyloid net in the gut mucosa for trapping bacteria (Fowler et al, 2006;Maji et al, 2009;Chu et al, 2012;Li et al, 2012). In addition to our studies of CRES amyloid in the epididymal lumen, we have previously shown that the mouse egg zona pellucida is an amyloid, as is part of the mouse sperm acrosomal matrix, demonstrating that functional amyloids are a normal component of the reproductive tract with integral roles in sperm maturation and fertilization (Guyonnet et al, 2014;Egge et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some peptides that lack bactericidal activity have been found to have a range of activities such as binding to bacterial cells and forming self-assembled nanonets that prevent bacterial proliferation in host tissues (Chu et al, 2012). Other defensins from plants have been shown to cause cell lysis by directly binding to the plasma membrane phospholipid phosphatidylinositol 4,5-bisphosphate (Poon et al, 2014).…”
Section: Discussionmentioning
confidence: 99%